Kesebelasan gen halilintar - Faruk, Lenggogeni (PT Suqma Corpora Indonesia, 2015)
11 Kids without baby sitter, without nanny, without maid. Orang tua dengan 6 putra dan 5 putri bekerja sama as a team organizing home like a hotel yang ada room service, house keeping, kitchen, laundry, etc.